Mapping European security after Kosovo - Medvedev, Sergei (Manchester University Press, 2002)
This book provides new and stimulating perspectives on how Kosovo has shaped the new Europe. It breaks down traditional assumptions in the field of security studies by sidelining the theoretical worldview that underlies mainstream strategic thinking on recent events in Kosovo. The contributors challenge the epistemological definition of the Kosovo conflict, arguing that we should not only be concerned with the 'Kosovo out there', but also with the debate about what counts as security and how our definition of security is shaped by various power and knowledge interests in Kosovo. They have adopted an innovative critical approach, both re-essentialising and deconstructing orthodox assumptions about the nature of European and global security. This book is perfect for final year undergraduates, postgraduates and academics in the field of security studies and international politics.